2017
DOI: 10.1038/s41598-017-17069-8
|View full text |Cite
|
Sign up to set email alerts
|

The Posterior Insula Shows Disrupted Brain Functional Connectivity in Female Migraineurs Without Aura Based on Brainnetome Atlas

Abstract: Long-term headache attacks may cause human brain network reorganization in patients with migraine. In the current study, we calculated the topologic properties of functional networks based on the Brainnetome atlas using graph theory analysis in 29 female migraineurs without aura (MWoA) and in 29 female age-matched healthy controls. Compared with controls, female MWoA exhibited that the network properties altered, and the nodal centralities decreased/increased in some brain areas. In particular, the right poste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 74 publications
3
30
0
Order By: Relevance
“…Our data showed that the right posterior insula had increased DC as well as increased FC with the postcentral gyrus, SMA/PCL, fusiform gyrus, and temporal pole in migraine patients relative to controls. Right-sided lateralization of insula abnormalities has also been observed in a number of structural and functional studies of pain or migraine (Symonds, 2006 ; Maleki et al, 2012 , 2015 ; Zhang et al, 2017 ). Partially consistent with our results, the posterior insula showed reduced habituation associated with amplification of trigeminal brainstem input in a previous study on episodic migraine without aura (Lee et al, 2017 ).…”
Section: Discussionmentioning
confidence: 72%
“…Our data showed that the right posterior insula had increased DC as well as increased FC with the postcentral gyrus, SMA/PCL, fusiform gyrus, and temporal pole in migraine patients relative to controls. Right-sided lateralization of insula abnormalities has also been observed in a number of structural and functional studies of pain or migraine (Symonds, 2006 ; Maleki et al, 2012 , 2015 ; Zhang et al, 2017 ). Partially consistent with our results, the posterior insula showed reduced habituation associated with amplification of trigeminal brainstem input in a previous study on episodic migraine without aura (Lee et al, 2017 ).…”
Section: Discussionmentioning
confidence: 72%
“…Small-World models are characterized by high clustering and short path length; therefore, they are widely used in neural networks, which confers the ability for specific information processing in a modular way among neighboring regions even over the whole network [47]. Deviation of the functional network topology in migraineurs has been demonstrated by other studies [48, 49]. In the present study, the abnormal networks can be characterized as increased degree in the theta, beta, and gamma bands; increased path length in the beta, gamma, and ripple bands; increased strength in the beta and gamma bands; and finally, an increased clustering coefficient in the theta, beta, and gamma bands.…”
Section: Discussionmentioning
confidence: 99%
“…Structural MR studies have shown cortical visual areas changes in MwA, MwoA, or both subgroups in V2, V3A, V5 (also known as MT) [7,11,[15][16][17]. Functional neuroimaging evidence over the past decade has shown specific brain function in migraine patients is abnormal compared to normal controls [10,12,[18][19][20][21][22]. Some studies have shown "overactivity" of the visual cortex during migraine episodes [23] and interictal interval [24].…”
Section: Introductionmentioning
confidence: 99%